Translation machine: an introduction - Fuzianti, D; Tawami, T; Mardiyani, R; Rahmatillah, R; Saputra, H (Yayasan Mitra Persada Nusantara, 2022)
Technology is a benchmark for universal development by providing easy access for users. Technology has also spread to the realm of languages where online translation tools make communication across languages easier. This research aims to provide information about the accuracy of translation in the Indonesian to English using Google Translation and Papago Naver to examine the language use of translation tools for websites. In this paper, we used qualitative methods to support our analysis by comparing both selected tools. The results indicated the quality of online translation tools is ineligible as the language used on the website. Several errors were found, mostly because the system could not recognize pronouns and only translated as according to their literal meaning without considering lexicosemantic. In conclusion, both translation tools have different accuracy levels to translate a variety of text and 50% of it is considered inaccurate which needs to be corrected by replacing each word and editing the whole text. This research is expected to facilitate the translation of words or sentences on a small or large scale and to provide another alternative on switching language use.